Mercosur and unasur: a look into the regional integration at the beginning of the xxith century (2011)
During the first half of the XXth Century, projects of integration in Latin America, in the light of the concept of .Pan-Americanism., and closely related to the emergence of the U.S. as a global power, were proposed. For the second half of the century, after the Creation of the Economic Commission for Latin America (CEPAL, in Spanish), projects appeared that, under the last name of .Latin American. (ALALC, ALADI), reflected the renewal of integration purposes. Nevertheless, difficulties for the regional community reappeared. At present, there are two outstanding projects under formation: The Southern Common Market (Mercosur, in 1994) that has survived in spite of varied difficulties, many of these explained by its recent constitution. And a little while ago, a new project appeared: The South American Union of Naciones, (Unasur, in 2008 ), sharing goals with the Bolivarian Alternative for the Peoples of our America (ALBA, in 2004). These ambitious projects interact among the varied political ideological spectrum of the South American region. The objective in this article is to present an analysis of the two recent integration projects, bearing in mind the political ideological context of the region and its repercussion in their processes of formation.